(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
One of the developments in technology is the use of E-Wallets. The existence of discountson online purchases is one of the influences on impulse buying behavior. The purpose of this study is to collect data and analyze the relationship or influence of E-Wallet and discounts on impulse buying in the marketplace. This research is a quantitative study to determine the effect of E-Wallet and discounts on impulse buying in the marketplace. Data collection was carried out by collecting information through a questionnaire. The population in this study are students who use E-Wallet, often make online purchases in the marketplace and often use discounts in the marketplace. The sampling method used is Purposive Sampling. This is a method that requires samples that own and use E-Wallets, often make online purchases in the marketplace, often use discounts on purchases in the marketplace, and there is a limited number of samples. The consideration in determining the sample in Purposive Sampling is the suitability of the characteristics of the respondent with the research objectives. The results showed that the E-Wallet variable had a positive and insignificant effect on Impulse Buying. While the Discount variable has a positive and significant effect on Impulse Buying.